Lifestyle Modifications and Nutritional Interventions in Aging-Associated Cognitive Decline and Alzheimer’s Disease - Bhatti, Gurjit Kaur; Reddy, Arubala P.; Reddy, P. Hemachandra; Bhatti, Jasvinder Singh (Frontiers in Aging Neuroscience, 2020)
Alzheimer's disease (AD) is one of the incurable neurodegenerative diseases characterised by accumulation of amyloid-beta (plaques) and tau hyperphosphorylation (neurofibrillary tangles) in the brain followed by neuronal death, cognitive decline and memory loss. The high prevalence of AD in the developed world has become a major public health challenge associated with social and economic burden on individuals and society. Due to limited options of early diagnosis and exact pathophysiology of the AD, finding effective therapeutic strategies has become a great challenge. Several possible risk factors associated with AD pathology have been identified; however their conclusive role is still unknown. Recent clinical trials of the drugs targeting amyloid-beta and tau are failing in finding any cure for the AD pathology. Therefore effective preventive strategies should be followed to reduce the exponential increase in the prevalence of cognitive decline and dementia, especially AD. Although the search for new therapeutic targets is a great challenge for the scientific community, the role of lifestyle interventions and nutraceuticals in the prevention of many metabolic and neurodegenerative diseases are highly appreciated in the literature. In this article, we summarised the molecular mechanisms involved in AD pathology and possible ameliorative action of lifestyle and nutritional interventions including diet, exercise, calorie restrictions, and various bioactive compounds on cognitive decline and dementia. This article will provide insights into the role of non-pharmacologic interventions in modulation of AD pathology, which may offer benefit in improving the quality of life by reducing the cognitive decline and incident AD.